A Feasibility Study On Using Beneficiated Slimes And Fines For Pelletization - S. K. Chaurasiya (International Mineral Processing Congress, 2012)
o meet the ever increasing demand of iron oxide feed stock for rapidly growing domestic steel industries and to effectively manage the depleting reserve of high grade lumpy iron ore, Pelletization of iron ore fines/slimes are expected to play a dominant role in the near future. Use of pellets will also enable the blast furnace operator to achieve higher levels of productivity with lowering of operating cost. The effective utilization of Iron Ore Slimes is important not only from the point of view of optimum utilization of Iron values in the mined ore but also for preventing environmental pollution. A significant amount of slime is being accumulated at the tailing dam of one of the iron ore mines and with the present scale of operation the tailing dam will be filled in another 10 years. Hence to increase the life of tailing dam and for better utilization of the iron values a study has been carried out for the suitability of pellet manufacturing with slimes and fines at our laboratory. The pelletization studies are aimed for optimization of various parameters for production of Blast furnace/ DR grade pellets from beneficiated slimes and Fines. This paper attempts to describe the production of blast furnace grade pellets from beneficiated slime and fines and its characterizations.